Human Capital Management Strategy and Human Resources Changing Nature - Suhairi Suhairi; Sri Rahmadhani; Annio Indah Lestari Nst; Sri Rahma (Journal of Management and Business Innovations, 2020)
The success of an organization unites the commitments and consequences of human resource management, which is capable of changing employee building in the character of additional individual value of human capital (human capital) as an investment in company assets in a superior labor market. The purpose of this paper is to study literature review to review human capital management strategies changes in the nature of human resources. In discussing HR governance, strategy, management and human capital, leadership and factors of human capital income. The findings of the study show that there are still many irregularities in organizations with poor governance due to the lack of an unclear policy, process, and procedure. Improving the management of employees, who are not only employees, to increase the productivity of the investment company "employees", preparation for the development of skills, knowledge and competencies, education to create superior human capital.Keywords: Human capital, human resources, streategy